Lithiophilic Sites in Doped Graphene Guide Uniform Lithium Nucleation for Dendrite‐Free Lithium Metal Anodes - Zhang, Rui; Chen, Xiao‐Ru; Chen, Xiang; Cheng, Xin‐Bing; Zhang, Xue‐Qiang; Yan, Chong; Zhang, Qiang (Angewandte Chemie International Edition, 2017)
Lithium (Li) metal is the most promising electrode for next‐generation rechargeable batteries. However, the challenges induced by Li dendrites on a working Li metal anode hinder the practical applications of Li metal batteries. Herein, nitrogen (N) doped graphene was adopted as the Li plating matrix to regulate Li metal nucleation and suppress dendrite growth. The N‐containing functional groups, such as pyridinic and pyrrolic nitrogen in the N‐doped graphene, are lithiophilic, which guide the metallic Li nucleation causing the metal to distribute uniformly on the anode surface. As a result, the N‐doped graphene modified Li metal anode exhibits a dendrite‐free morphology during repeated Li plating and demonstrates a high Coulombic efficiency of 98 % for near 200 cycles. The matrix: Nitrogen‐doped graphene is used as the Li plating matrix to regulate Li metal nucleation and suppress dendrite growth. The N‐containing functional groups in the N‐doped graphene are lithiophilic, which guide the Li nucleation and give a uniform distribution of Li on the anode surface. The dendrite‐free lithium‐metal anodes exhibit an impressive electrochemical performance.